Calcium-Permeable AMPA Receptors in the Retina - Diamond, Jeffrey S. (Frontiers in Molecular Neuroscience, 2011)
The retina transforms light entering the eye into a sophisticated neural representation of our visual world. Specialized synapses, cells and circuits in the retina have evolved to encode luminance, contrast, motion and other complex visual features. Although a great deal has been learned about the cellular morphology and circuitry that underlies this image processing, many of the synapses in the retina remain incompletely understood. For example, excitatory synapses in the retina feature the full panoply of glutamate receptors, but, with few exceptions (DeVries, 2000; Sagdullaev et al., 2006), specific roles for different receptor subtypes are unclear. In this brief review, I will discuss recent progress toward understanding how Ca2+-permeable AMPA receptors (CP-GluARs) contribute to synaptic transmission and newly discovered forms of synaptic plasticity in the retina.